Capsicum-Colletotrichum interaction: Identification of resistance sources and quantification of secondary metabolites in unripe and ripe fruits in response to anthracnose infection - Baba, Viviane Yumi; Constantino, Leonel Vinicius; Ivamoto, Suzana Tiemi [UNESP]; Paladini Moreira, Aline Fabiana; Madeira, Tiago Bervelieri; Nixdorf, Suzana Lucy; Rodrigues, Rosana; Azeredo Goncalves, Leandro Simoes (Elsevier B.V., 2019)
Anthracnose, caused by Colletotrichium species complex, is one of the main fungal diseases in pepper (Capsicum spp.) crops, resulting in extensive fruit losses during pre- and post-harvesting. Plants have structural and biochemical defense mechanisms produced before and/or after the pathogen attack. Biochemical defense involve the production of compounds that accumulate at the site of infection and are toxic to the pathogen. However, the accumulation and biosynthesis of these compounds during Capsicum-Colletotrichum interaction, especially during fruit development stages remain poorly understood. In order to identify potential resistant genotypes and to improve our knowledge about the metabolites produced by pepper fruits against fungus infection, we inoculated unripe and ripe fruits of 59 accessions of Capsicum spp. with C. gloeosporioides and analyzed the disease severity during 8 days after inoculation. In this study, we observed a wide variability of fungus resistance response in unripe and ripe fruits of Capsicum spp. accessions, and ripe fruits presented greater resistance to anthracnose than unripe. Six accessions (GBUEL06, GBUEL28, GBUEL73, GBUEL87, GBUEL104 and GBUEL106) were considered as resistant for both fruits development stages and have potential to be used in future breeding programs. In addition, we selected two C. annuum accessions GBUEL103 (susceptible) and GBUEL104 (resistant), to describe the histological aspects of C. gloeosporioides infection in pepper fruits, followed by the quantification of secondary metabolites produced during this plant-pathogen interaction, using light microscopy and ultra-high performance liquid chromatography (UHPLC), respectively. The quantification of secondary metabolites produced in pepper fruits during fungus infection showed different values according genotype characteristic (susceptible or resistant), fruit development stages (unripe and ripe) and time (1st and 8th day post-inoculation). Interestingly, high concentrations of caffeic and chlorogenic acid were quantified in unripe and ripe fruits characterized as resistant genotype, showing that these biochemical compounds are putatively involved in fruit defense mechanism in response to anthracnose disease.
Keywords: Peppers; Colletotrichum gloeosporioides; Fruit ripening; Defense mechanisms; Phenolic compounds